2003
DOI: 10.1172/jci200320401
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for pituitary tumorigenesis: the plastic pituitary

Abstract: The anterior pituitary gland integrates the repertoire of hormonal signals controlling thyroid, adrenal, reproductive, and growth functions. The gland responds to complex central and peripheral signals by trophic hormone secretion and by undergoing reversible plastic changes in cell growth leading to hyperplasia, involution, or benign adenomas arising from functional pituitary cells. Discussed herein are the mechanisms underlying hereditary pituitary hypoplasia, reversible pituitary hyperplasia, excess hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
119
0
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(127 citation statements)
references
References 145 publications
0
119
0
8
Order By: Relevance
“…Growth is mainly due to an increase in cell number and size. Between 10 and 30% of the proliferating cells contain hormone immunoreactivity (as studied in the rat) [[7, 8, 20, 23, 28, 31], and references therein], indicating that only part of the new hormonal cells develop by ‘self-mitosis’ of already differentiated cells. This finding further implies that most mitotic activity takes place in undifferentiated cells, and it has repeatedly been suggested that the cells that form shortly after birth, are produced by recruitment (proliferation and differentiation) of stem cells [7, 20, 21, 23, 29].…”
Section: Pituitary Stem Cells: Support From Developmental and (Patmentioning
confidence: 99%
See 4 more Smart Citations
“…Growth is mainly due to an increase in cell number and size. Between 10 and 30% of the proliferating cells contain hormone immunoreactivity (as studied in the rat) [[7, 8, 20, 23, 28, 31], and references therein], indicating that only part of the new hormonal cells develop by ‘self-mitosis’ of already differentiated cells. This finding further implies that most mitotic activity takes place in undifferentiated cells, and it has repeatedly been suggested that the cells that form shortly after birth, are produced by recruitment (proliferation and differentiation) of stem cells [7, 20, 21, 23, 29].…”
Section: Pituitary Stem Cells: Support From Developmental and (Patmentioning
confidence: 99%
“…Possible mechanisms for cell genesis, as applicable to all tissues, include mitosis of already differentiated cells, transdifferentiation between distinct cell phenotypes, and maturation (differentiation) of stem and progenitor cells. All three processes have in the pituitary field their advocates, and all are supported, although most of the time only circumstantially, by literature data [[5,6,7,8,9,10,11,12,13,14,15,16,17,18], and references therein]. Most likely, all three processes combine their effects in dynamic cell adaptations, but a single mechanism may predominate depending on the particular (patho-)physiological situation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations